An Optical Coherence Tomography Assessment of Stent Strut Apposition Based on the Presence of Lipid-Rich Plaque in the Carotid Artery. (December 2015) - Liu, Rui; Jiang, Yongjun; Xiong, Yunyun; Li, Min; Ma, Minmin; Zhu, Wusheng; Yin, Qin; Li, Wei; Xu, Gelin; Liu, Xinfeng
Purpose: To evaluate the rate of stent malapposition, plaque prolapse, and fibrous cap rupture detected by optical coherence tomography (OCT) after carotid artery stenting (CAS) based on the presence of lipid-rich plaque, which may be associated with acute stent thrombosis.Methods: A retrospective study was conducted involving 26 consecutive patients who underwent CAS with OCT imaging acquired before stent deployment and after stent dilation. Adequate imaging quality could not be obtained in 6 patients (out-of-screen images and residual blood), which left 20 patients (mean age 63 years; 13 men) for analysis. Plaque characteristics were determined from 500 selected OCT cross sections; a lipid-rich plaque was defined by lipid present in ≥2 quadrants. Cross-sectional OCT images within the stented segment were evaluated at 1-mm intervals for the presence of malapposition, plaque prolapse, and fibrous cap rupture. The data were compared between patients with and without lipid-rich plaques. The patients were examined at 6 months to determine the degree of in-stent restenosis (ISR).Results: Patients with lipid-rich plaque demonstrated a higher rate of embedded stent struts (29.4% vs 23.7%, p<0.001) and a lower rate of well apposed struts (54.6% vs 59.6%, p<0.001) compared to patients with non–lipid-rich plaque. Rates of plaque prolapse (65.5% vs 49.1%, p<0.001) and fibrous cap rupture (65.5% vs 49.1%, p<0.001) were significantly higher in patients with lipid-rich plaque. ISR ranged from none to 42% in 12 patients; malapposed stent struts and fibrous cap ruptures were not more frequent in the patients with obvious ISR. The 8 patients with no obvious restenosis still had malapposed struts, embedded struts, plaque prolapse, and fibrous cap rupture.Conclusion: Embedded stent struts, plaque prolapse, and fibrous cap rupture were more frequent and well-apposed stent struts were less frequent after CAS in patients with lipid-rich plaque.